2022
DOI: 10.3390/hydrology9040062
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Hydrologic Performance and Cost-Effectiveness of LID in a Residential Park Area Using a Decentralized Design Approach

Abstract: Low Impact Development (LID) is one of the current research interests toward green infrastructures and urban flood control that have the capability to return developed watersheds to pre-development hydrological conditions, bringing numerous water quantity and quality benefits, while being cheaper than their traditional counterparts. However, there is a current research gap about LIDs within tropical regions. This study aims to evaluate the cost efficiency of LID scenarios in varying surface areas through a cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
(88 reference statements)
1
5
0
Order By: Relevance
“…In order to graphically summarize the performances (reduction percentages) found for the different metrics in the seven typologies, Table 8 presents a summary of the values found. The analysis for the total runoff volume reductions (10%-30%) identified similar performances for the RG, BC, and PP as those reported in previous studies (Arjenaki et al 2021;Garbanzos and Maniquiz-Redillas 2022;Jato-Espino et al 2016;Bai et al 2018), but somewhat limited for the rest of the typologies (< 5%). At the same time, the decrease in pollutant (TSS, NT, and TP) loads was high for all the typologies (> 90%).…”
Section: Overall Performancessupporting
confidence: 79%
See 1 more Smart Citation
“…In order to graphically summarize the performances (reduction percentages) found for the different metrics in the seven typologies, Table 8 presents a summary of the values found. The analysis for the total runoff volume reductions (10%-30%) identified similar performances for the RG, BC, and PP as those reported in previous studies (Arjenaki et al 2021;Garbanzos and Maniquiz-Redillas 2022;Jato-Espino et al 2016;Bai et al 2018), but somewhat limited for the rest of the typologies (< 5%). At the same time, the decrease in pollutant (TSS, NT, and TP) loads was high for all the typologies (> 90%).…”
Section: Overall Performancessupporting
confidence: 79%
“…Although the previous, and some other case studies have successfully implemented and validated SUDS urban models (e.g., Kong et al 2017;Maftuhah et al 2018;Rujner et al 2018;Garbanzos and Maniquiz-Redillas 2022;Arjenaki et al 2021;Ma et al 2022), there are still gaps regarding modeling technicalities and aspects that have not been addressed so far, such as trains modeling, continuous-long term modeling, effect of temporal and spatial scale, or performance of different typologies. Previous studies have highlighted the importance of systematically studying the sensitivity of the models to specific SUDS design parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed that LIDs (Sustainable Drainage Systems, SUDs) have a positive impact on the hydrological and hydraulic load of traditional urban drainage systems; however, the biggest reduction was achieved in cases of small, relatively frequent rainfall events and more pervious soil types [199][200][201][202][203][204]. In case of extreme rainfall events, such a reduction in flow (water volume) is very limited and sensitive to local conditions.…”
Section: Rainfall-runoff Models and The Decision-making Processmentioning
confidence: 99%
“…This study used the Weibull plotting position, a probability distribution function to fit distributions in hydrology (Murugappan, Sivaprakasam & Mohan, 2017;Adeboye & Alatise, 2007), to obtain the 90 th percentile of the collected rainfall for simulations. This 90 th percentile of total rainfall was selected as it has been the standard for many LID manuals (EPA, 2009; Ministry of the Environment & Climate Change, 2016) and some studies This journal is ⓒ Academic Society for Appropriate Technology 2022 (Frias & Maniquiz-Redillas, 2021;Garbanzos & Maniquiz-Redillas, 2022) for rainfall estimation in design. Equation (1) shows the Weibull distribution method formula.…”
Section: Rainfall Datamentioning
confidence: 99%
“…The Weibull distribution method performed showed that the 90 th percentile of the 40-year historical rainfall was approximately 16.64 mm. This was then distributed over 24 hours using the triangle method as used by Frias & Maniquiz-Redillas (2021) and Garbanzos & Maniquiz-Redillas (2022) and was utilized as the sole rainfall scenario for all simulations.…”
Section: Rainfall Characteristicsmentioning
confidence: 99%